2014
DOI: 10.1002/hbm.22600
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pediatric epilepsy on a language connectome

Abstract: This study introduces a new approach for assessing the effects of pediatric epilepsy on a language connectome. Two novel data-driven network construction approaches are presented. These methods rely on connecting different brain regions using either extent or intensity of language related activations as identified by independent component analysis of fMRI. An auditory word definition decision task paradigm was used to activate the language network for 29 patients and 30 controls. Evaluations illustrated that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 82 publications
(131 reference statements)
0
14
0
Order By: Relevance
“…The contrast can also be drawn to see if such connectivity maps could enhance the prospects of a diagnosis with the ability to augment other methods seeking a similar goal. Such methods could compare these connectivity maps in relation to specific frequency and temporal features [6,10] or associate them to fMRI data using the connectome, decision functions or PCA [18,54,59] for an optimal classification process. Through the application of developing scalp EEG based connectivity; these initial results did support the hypothesis that pediatric epilepsy disease impacts the connectivity patterns significantly relative to the control population.…”
Section: Resultsmentioning
confidence: 99%
“…The contrast can also be drawn to see if such connectivity maps could enhance the prospects of a diagnosis with the ability to augment other methods seeking a similar goal. Such methods could compare these connectivity maps in relation to specific frequency and temporal features [6,10] or associate them to fMRI data using the connectome, decision functions or PCA [18,54,59] for an optimal classification process. Through the application of developing scalp EEG based connectivity; these initial results did support the hypothesis that pediatric epilepsy disease impacts the connectivity patterns significantly relative to the control population.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to language, random network organization and low integration predicted poorer expressive language outcome, explaining 73% of the variance in language decline following both left and right ATL (Doucet, Pustina, et al, 2015). In a study that examined localization-related epilepsy in children, Eddin et al (2014) derived graph theory measures from fMRI data and examined global and local language networks. They found globally decreased efficiency in language network connectivity in pediatric patients when compared to controls.…”
Section: New Analytic Models For Evaluating Network Disruption In mentioning
confidence: 99%
“…While small-world network topology was observed in both the pediatric patients and the control group, network activation in the pediatric epilepsy group was more random. Overall, the control group was observed to efficiently activate a smaller, partitioned network to complete a language task while the pediatric epilepsy group utilized the whole brain for the same task (Eddin et al, 2014). Kellerman et al (2015) similarly found decreased efficiency and organization as well as poor segregation of cognitive network modules in the pediatric epilepsy population (Kellermann, Bonilha, Lin, & Hermann, 2015).…”
Section: New Analytic Models For Evaluating Network Disruption In mentioning
confidence: 99%
“…Considering the fact that Epilepsy is a complex disease with multifactorial causes, makes the diagnostic process much more complicated than simply relying on solely model driven knowledge. Furthermore, human brain involves a complex web of neuronal connectivity and discrete anatomical regions that function together to generate brain activity (Lowe, Mock et al 1998;Eddin, Wang et al 2014). …”
Section: Magnetoencephalography (Meg) and Functional Magnetic Resonanmentioning
confidence: 99%
“…AD and AC subjects had a neurological and medical evaluation by a physician acoording to the neuropsychological tests (Duara, Loewenstein et al 2010). Structural MRI for pediatric subject groups, PE and PC, were collected by a multisite consortium and repository (Lahlou, Guillen et al 2006)for pediatric epilepsy to study the Age Female/Male PE (n = 13) 13 ± 2.93* 8/5 PC (n = 18) 11 ± 1.26 8/10 AD (n=11) 81 ± 9.31 6/5 AC (n=11) 71 ± 6.21 9/2 effects of pediatric epilepsy on the functionality of the brain as well as on structural impacts (Guillen, Adjouadi et al 2009;Eddin, Wang et al 2014). …”
Section: Subjects and Imagesmentioning
confidence: 99%